2012
DOI: 10.1038/bjc.2012.306
|View full text |Cite
|
Sign up to set email alerts
|

Serum markers lactate dehydrogenase and S100B predict independently disease outcome in melanoma patients with distant metastasis

Abstract: Background:Established prognostic factors are of limited value to predict long-term survival and benefit from metastasectomy in advanced melanoma. This study aimed to identify prognostic factors in patients with distant metastasis.Methods:We analysed overall survival of 855 institutional melanoma patients with distant metastasis by bivariate Kaplan–Meier survival probabilities and multivariate Cox hazard regression analysis.Results:Serum lactate dehydrogenases (LDH), S100B, the interval between initial diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
83
2
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(93 citation statements)
references
References 35 publications
6
83
2
1
Order By: Relevance
“…These biomarkers were more as in the subgroup of stage I to stage III patients (hazard ratio 2.28; p < 0.0001) independent from other prognostic factors. In prior studies, we demonstrated that S100B and LDH had independent impact on prognosis of patients with distant metastasis and the combined analysis of both markers might be used to select patients for metastasectomy [7,8]. However, despite this large evidence, no worldwide consensus exists on its implementation in the routine clinical setting in melanoma patients.…”
Section: Introductionmentioning
confidence: 91%
“…These biomarkers were more as in the subgroup of stage I to stage III patients (hazard ratio 2.28; p < 0.0001) independent from other prognostic factors. In prior studies, we demonstrated that S100B and LDH had independent impact on prognosis of patients with distant metastasis and the combined analysis of both markers might be used to select patients for metastasectomy [7,8]. However, despite this large evidence, no worldwide consensus exists on its implementation in the routine clinical setting in melanoma patients.…”
Section: Introductionmentioning
confidence: 91%
“…Similar associations with survival have been established in chronic myeloid and lymphocytic leukaemias (Weinberg et al, 2007;Goldaniga et al, 2008) and small cell lung cancer (SCLC) (You et al, 2008;Danner et al, 2010). In recent clinical trials, elevated serum LDH has been shown as an independent predictor of overall survival in advanced or metastatic cancer of the breast (Brown et al, 2012), prostate (Scher et al, 2009;Gravis et al, 2014), colorectum (Bar et al, 2014), oesophagus (Polee et al, 2003), pancreas (Tas et al, 2001), ovary (Schneider et al, 1998), nasopharynx (Jin et al, 2013), gastric adenocarcinoma (Sougioultzis et al, 2011), hepatocellular carcinoma (HCC) (Faloppi et al, 2014), renal cell carcinoma (Armstrong et al, 2012) and melanoma (Balch et al, 2004;Weide et al, 2012). The inverse association with overall survival in solid tumours were shown in a recent meta-analysis, with HR for overall death of 1.7 (95% CI: 1.62-1.79) (Petrelli et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Weide et al assessed the use of biomarker in melanoma patients with distant metastases. Serum markers LDH and S100B were found to be independent prognostic factors in melanoma patients with distant metastases, and both factors were associated with similar hazard ratios (Weide et al 2012).…”
Section: Biomarkers and Monitoring Of Vemurafenib Treatmentmentioning
confidence: 72%